The effect of gender differences on dentist’s performance (a study in health centers in East Java) - Titiek Berniyanti; Kromodiharjo Sudiyono (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Gender is a social relationship concept that differentiates role and function between man and women. Equality of rights and obligations between man and woman have been normatively guaranteed and the Constitution does not explicitly discriminate the rights and obligations of woman in law and government, in occupation and decent life, in politics, in religion and beliefs, and in national defend. Related with gender perspective, the need of health worker especially dentist worker has to be determined and planned properly. The productivity is one of the factor on dentist worker, that affect on the quality of health delivary. Some companies try to increase efficiency in performing their activities and try to measure activities they do. In this case, time & motion study method is one of the solutions to help the company measuring their activity. Using these techniques, company can measure the productivity of resources used for every activity. In order to get better performance in cost reduction, the company should assign their cost to the product resulted. Determination of the Standart time to work is one of the method that contain high value of efeciency to gain the productivity. The aim of this study was to learn how gender has an effect on dentist’s work performance. The time of completing dentist’s task i.e: teeth extraction were measured and the standard time were determined. In addition the patient’s respond were measured through questionair. This study was conducted in East Java. The conclusion of this study revealed that there was no difference of work performance between male and female dentist’s.